Bending the curve: force health protection during the insertion phase of the Ebola outbreak response. Issue 3 (2nd June 2015) - Bailey, Mark S; Beaton, K; Bowley, D; Eardley, W; Hunt, P; Johnson, S; Round, J; Tarmey, N T; Williams, A
Abstract : After >10 years of enduring operations in Iraq and Afghanistan, Defence Strategic Direction is returning to a contingency posture. As the first post-Afghanistan operation, in September 2014, a UK Joint Inter-Agency Task Force deployed to Sierra Leone in response to the Ebola virus disease (EVD) epidemic in West Africa. The aims were expanding treatment capacity, assisting with training and supporting host nation resilience. The insertion phase of this deployment created a unique set of challenges for force health protection. In addition to the considerable risk of tropical disease and trauma, deployed personnel faced the risks of working in an EVD epidemic. This report explores how deployed medical assets overcame the difficulties of mounting a short-notice contingent operation in a region of the world with inherent major climatic and health challenges.